In vitro efficacy of sulbactam combined with ampicillin against anaerobic bacteria. - Wexler, H M (1985)
An ampicillin-sulbactam combination was compared with ampicillin alone, chloramphenicol, clindamycin, and metronidazole against 272 strains of anaerobic bacteria. Chloramphenicol and ampicillin-sulbactam were the most effective, inhibiting 98 to 99% of strains tested at breakpoint (16 micrograms/ml). The combination of sulbactam and ampicillin was much more effective than ampicillin alone against Bacteroides fragilis strains but did not differ substantially from ampicillin alone against Fusobacterium spp., gram-positive rods, and gram-positive cocci.